METHOD OF DEFINITION OF PROBABILITY-TIME CHARACTERISTICS OF LAYER OF SERVICES AND APPLICATIONS SERVERS OF IMS - Kniazieva, N. O.; Shestopalov, S. V.; Sirenko, O. I. (Radio Electronics, Computer Science, Control, 2019)
Context. Article is devoted to development of a method of definition of probability-time characteristics of layer of services and applications servers of IMS. It is shown that constantly growing a variety of services which IMS, and increase in demand for them among users is capable to provide and also the fact that with development of telecommunications the increasing attention is paid to quality of providing services – QoS, the problem of assessment of quality of providing services causes relevance of development of a method of definition of probability-time characteristics of layer of services and applications servers of IMS. Objective. Develop a method of definition of probability-time characteristics of layer of services and applications servers of IMS taking into account different types of services which IMS is capable to provide. Method. It is considered architecture of IMS. The main attention is paid to the layer of services and applications servers. For development of a method of definition of probability-time characteristics of layer of services and applications servers of IMS it is offered to use approaches of the queuing theory and the tensor analysis of networks. The offered method represents the sequence of stages which execution allows to define structural blocks of layers of services and applications servers of IMS which are responsible for providing services of different types; present call session control function and the layer of services and applications servers in the form of separate laid on network – initial queuing network; for use of a planimetric method to enter the imagined branch which creates the closed circuit; enter planimetric intensity and define their directions; define a transition matrix from initial network to primitive network; present the invariant equation for initial network; define planimetric intensity and on their basis to calculate intensity of receipt of requests for services and loadings of servers in initial network. As a result – to receive expressions for calculation of probability- time characteristics of layer of services and applications servers. Results. The method of definition of probability-time characteristics of layer of services and applications servers of IMS on the basis of approaches of the queuing theory and tensor analysis of networks which allows to consider different types of services which IMS is capable to provide is offered. Conclusions. The method of definition of probability-time characteristics of layer of services and applications servers of IMS will allow designers IMS to calculate probability-time characteristics at early stages of the project that will allow to define the necessary network resources for ensuring required value of quality of providing services of different types. Further, at development of the offered method, at a research of layer of services and applications servers of IMS for the purpose of definition of probability-time characteristics accounting of self-similarity of a flow of requests for services and restrictions of a buffer memory of servers is reasonable.